SISTEM RUJUKAN BERJENJANG BPJS KESEHATAN - Bobi Handoko; Sherly Mutiara; Cindi Febriani Pramita; Ade Novita Andriani (LPPM Universitas Awal Bros, 2021)
The lack of public understanding of the BPJS health tiered Referral System is a weakness that the community has. People who do not understand the BPJS health tiered referral system can experience deep obstacles in getting health services. In this article, the author describes the community service activities that have been carried out to increase public understanding of the BPJS health tiered referral system. This activity was carried out in the community area of ​​RW 001 Kel. Kulim district. Kulim Using the method of distributing brochures, lectures and Q&A. As for the results of this community activity, the community has been able to understand the BPJS Health tiered referral system. This activity can also help the community in obtaining health services.